NATURAL SUBSTRATES OF DIPEPTIDYL PEPTIDASE IV (Proceedings of the YSU B: Chemical and Biological Sciences, 2016)
A widely expressed multifunctional, membrane-anchored cell surface or in a soluble form in the plasma and other body fluids serine protease, dipeptidyl peptidase IV (DPPIV), cleaves dipeptide from peptides containing proline or alanine in the N-terminal penultimate position. Several important regulatory peptides have been identified as DPPIV substrates, including neuropeptides, chemokines, and the incretin hormones, which share this conserved sequence at their N-termini. Natural substrates of DPPIV are involved in immunomodulation, psycho/neuronal modulation and physiological processes in general and the cleavage by DPPIV of these peptides resulted in their inactivation or degradation. Therefore, targeting of DPPIV and especially its proteolytic activity has much therapeutic potential. Some known and new natural substrates were discussed in this review.
Keywords: dipeptidyl peptidase IV, natural substrates of DPPIV, proteolytic activity of DPPIV, regulatory peptides, proline rich peptides, amyloid beta peptides, modification of bioactive peptides